Test for urine sugar using Clinitest Reagent Tablets (1970)
Series of photographs depicting a test for urine sugar using Clinitest Reagent Tablets manufactured by the Ames Company. Included in the photographs are directions for conducting the test and the color chart used to analyze the result.
Keywords: Diabetes; Urine--Analysis; Medical care; Diabetes--Treatment; Scientific apparatus and instruments; Medical supplies; Medical supplies industry